Evaluación de los cambios de cobertura a partir de un modelo hidrológico distribuido continuo en una cuenca rural del río san Jorge (Montelíbano, Córdoba). (2023)
This study aims to evaluate from continuous modeling, the hydrological response associated with the changes in vegetation cover presented in the rural basin of the San Jorge river at the height of the municipal seat of Montelíbano, Córdoba - Colombia for the years 2000, 2005, 2010 and 2018. Different techniques are applied to estimate the parameters adaptable to the modeling of the HEC-HMS program based on precipitation data and characteristics of the area, seeking to obtain similar and comparable flow results with the flow data series. Finally, the base flow parameters are estimated under the observation of the behavior, allowing them to be collated graphically, verifying the existing similarity of resulting flows in relation to the IDEAM information.